2008
DOI: 10.1016/j.jelekin.2006.09.015
|View full text |Cite
|
Sign up to set email alerts
|

The impact of computer display height and desk design on muscle activity during information technology work by young adults

Abstract: Computer display height and desk design are believed to be important workstation features and are included in international standards and guidelines. However, the evidence base for these guidelines is lacking a comparison of neck/shoulder muscle activity during computer and paper tasks and whether forearm support can be provided by desk design. This study measured the spinal and upper limb muscle activity in 36 young adults whilst they worked in different computer display, book and desk conditions. Display hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 33 publications
5
32
0
3
Order By: Relevance
“…According to one study, a higher screen height setting is positively correlated with a more erect neck angle (mean coefficient of correlation = 0.94), and EMG activity in the neck muscles is related to neck angle [6]. As a result, higher display locations (e.g., the top of the screen set at the participant's eye height) generally leads to neutral positions of the neck and head, while lower display locations (e.g., the screen set horizontally on the desk) leads to increasing flexed postures of the head and neck and is hypothesized to be a risky position, one that may cause heavy loads and strain on the muscles and thereby put users at risk of developing musculoskeletal discomfort or pain [3,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…According to one study, a higher screen height setting is positively correlated with a more erect neck angle (mean coefficient of correlation = 0.94), and EMG activity in the neck muscles is related to neck angle [6]. As a result, higher display locations (e.g., the top of the screen set at the participant's eye height) generally leads to neutral positions of the neck and head, while lower display locations (e.g., the screen set horizontally on the desk) leads to increasing flexed postures of the head and neck and is hypothesized to be a risky position, one that may cause heavy loads and strain on the muscles and thereby put users at risk of developing musculoskeletal discomfort or pain [3,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Working with notebook computers on the lap is associated with even more head and neck flexion [26,27]. This can be attributed to the lower screen height of a notebook computer, which has been reported several times as a significant factor for head and neck discomfort [28,29]. These postures can be improved by raising the monitor height with lap desks, inclines, a riser, or external monitor [23,26].…”
Section: Notebook Computingmentioning
confidence: 99%
“…For example, in our study population, a higher proportion of forearm supported strategies with keyboard use was observed in workers with the desk level above their elbow height (71.4%) than those of workers with the desk level at to be associated with higher screen height (Kietrys et al, 1998;Seghers et al, 2003;Straker et al, 2008a). This recommendation is based on the natural visual angle of the eyes even though these studies also observed less cervical extensor muscle activity (no differences in trapezius activity) with higher screen levels (Seghers et al, 2003;Straker et al, 2008b).…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies have investigated the relationship between workstation design and work task, postural adaptation, and muscle recruitment patterns during computer tasks (Aaras et al, 1997;Burgess-Limerick et al, 1999;Kotani et al, 2007;Stansfeld and Candy, 2006;Straker et al, 2008b; Grace P. Y. Szeto et al, 2005;Visser et al, 2000). Straker et al (2008b) found that gaze, head, neck and trunk angles became more pronounced the lower the computer screen height which was also associated with greater activity of the trapezius, cervical and 37 thorax erector spinae, muscles.…”
Section: Workplace Physical Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation